Road Accident Data Collection Systems in Developing and Developed Countries: A Review - Rabbani, M.B.A. (Penerbit UTHM, 2022)
Over time, the rate of road accidents is increasing day by day. Eventhough with various advancements, the developing countries are still struggling to eliminate this issue. One such possible solution could be adopting the advanced automated tools for the road accident data collection systems, based on which the policymakers can adopt the necessary strategies to avoid the accidents. In this manner, a review has been conducted where a comparison of road accident data collection systems was made between developing and the developed countries. It was observed that to establish a standardized system for road accident prevention, records from prior accidents play a key role in the evaluation and prediction of the accident, damage, and consequences. Moreover, the manual and digital approaches of data collection were highlighted, which revealed that digital approaches are reliable and time saving for data gathering and its compilation. This comparison is beneficial in terms of future developments in developing countries and the developed countries can act as a role model and their strategies can be implemented to reduce the accidents. Â© 2022 Universiti Tun Hussein Onn Malaysia Publisher's Office. All Rights Reserved.